2008
DOI: 10.21776/ub.jiae.2008.002.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Farmers in East Java: Institutional Arrangement Perspective

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Malang has experienced rapid economic growth of 5.61% in 2016 [ 18 ]. This rapid economic growth is due to changes in the structure of the industry from agriculture such as farming of cane and vegetables to tourism, trade, and Small and medium enterprises [ 18 19 ]. The residents seemed to go through rapid changes in dietary intakes.…”
Section: Methodsmentioning
confidence: 99%
“…Malang has experienced rapid economic growth of 5.61% in 2016 [ 18 ]. This rapid economic growth is due to changes in the structure of the industry from agriculture such as farming of cane and vegetables to tourism, trade, and Small and medium enterprises [ 18 19 ]. The residents seemed to go through rapid changes in dietary intakes.…”
Section: Methodsmentioning
confidence: 99%
“…However, Baksh and Yustika (2008) reported that the cooperatives usually bore on sugarcane farmers higher interest than legal rules. Besides, different conclusion reported by Dalilah (2013), that agricultural credit in KKPE program had not given significant implication on sugarcane farmers' income in Malang Regency.…”
Section: The Role Of Cooperatives In Sugarcane Agribusiness and Sugarmentioning
confidence: 99%
“…That sugarcane farmers adopting share-yield system rarely got any a Sugarcane price at sugar mill site (after harvested and transported). For selling types 3 and 4 sugarcane price was computed by considering conversion factor of sugarcane into sugar and molasses and with deduction of processing-related costs molasses share from sugar mill was also reported by Baksh and Yustika (2008). According to them, this happened due to lack of institutional arrangements.…”
Section: Selling Systemmentioning
confidence: 99%
“…Sugarcane farmers have an important role in supplying raw materials for sugar production but they are facing problems in declining sugarcane productivity and a lack of available arable land. Studies in Indonesia have only examined one aspect of sugar production in Indonesia, such as sugar mills [9], trade policy [10], farmers, land use optimization [11], bioethanol production [12], and cane farmers [13]. This paper provides a holistic review of the sugar cane production in Indonesia.…”
Section: Introductionmentioning
confidence: 99%